Teaching Strategies Strengthening EFL Learners’ Self-Confidence in Speaking Learning Dynamics - Kristian Wijaya (Educalingua, 2024)
Studies on effective speaking teaching strategies have caught mushrooming attention in these last two decades. This is not happening by incidental matters as globalized educationalists are still having arduous moments in devising more suitable, enjoyable, and relatable speaking learning strategies that can maximize EFL learners’ self-confidence. According to previous researchers, self-confidence is one of the propelling factors enabling EFL learners to gain more advanced communication proficiency levels since they possess a higher level of preparedness in confronting a wide variety of challenging speaking learning enterprises. This small-scale library study employed a thematic analysis approach while analyzing a certain number of identical research results produced by prior 25 speaking investigations published worldwide. By utilizing this research method, the researcher can potentially yield more relevant, contextual, and comprehensible research outcomes due to an iterative data analysis conducted before initiating more specific research theme groupings. Based on the thematically categorized research results, second language educators can progressively inculcate robust speaking self-confidence among EFL learners upon the activation of more authentic and enjoyable speaking learning activities. More comprehensive delineations regarding these two speaking learning methodologies can be discerned in the ensuing parts of this research paper